Teaching tools and techniques for efficient teaching and learning of computer programming for beginners using JAVA - Kannangara, Don Nimal Padmasiri (Curtin University, 2013)
Despite the educational research that has been carried out considering demographic, cognitive and social factors to improve teaching programming in the last decades, finding an effective teaching method is still a debatable issue among Java programming tutors. There are a number of basic concepts to be understood in learning a programming language. The teaching styles to be used to teach different concepts could vary due to the complexity and nature of the concept. This study was aimed at identifying such concepts and the preferred teaching style for teaching such concepts in the Java language. The results of a survey of the students who recently completed introductory level Java programming language revealed such concepts, and also the most preferred teaching style for each concept.This study also investigated the preferred learning styles for learners with artistic abilities and logical abilities. In addition, there have been many research projects based on Cognitive Load Theory (CLT) to investigate better ways of handing germane, intrinsic, and extraneous memory loads on the working memory of learners. The mental modeling technique has been found to be associated with most of the fundamental principles of the Cognitive Load Theory (CLT). This research also included the findings of classroom experiments using activities based on mental modeling, such as analogies, worked examples, and scaffolding, and adhering to the principles of CLT. The context for this research involved teaching Java programming concepts at the introductory level using low cost teaching tools. The study reports on the effects of such activities in teaching Java programming principles.